Variability of soil chemical properties and rice productivity in salt-affected soil in the north coastal rice field of Central Java, Indonesia - Kartikawati, Rina; Kurniasih, Budiastuti; Putra, Eka Tarwaca Susila; Hanudin, Eko (Journal of Degraded and Mining Lands Management, 2024)
A coastal rice field is generally characterized by salt-affected soil and low soil quality for rice cultivation. Identifying soil chemical properties in these areas is necessary to determine soil management options for rice production. Therefore, soil samples were collected from 33 sampling points in the Wedung Sub-district of Demak Regency in the late dry season of 2021 to evaluate the variation among soil chemical characteristics in a coastline rice field. Soil samples were obtained beneath the topsoil (0-20 cm soil depth) and observed for electrical conductivity, exchangeable potassium, sodium, calcium, magnesium, and cation exchange capacity. Soils in the research field were categorized as slightly salty (0.75-2 dS m-1) to lightly salty (2.0-4.0 dS m-1) with very high sodium (>2 cmol(+) kg-1). Exchangeable potassium was dominated by moderate (0.3-0.7 cmol(+) kg-1) and low categories (0.2-0.3 cmol(+) kg-1). Based on soil calcium-to-magnesium ratios, around 6% of all samples were classified as calcium-deficient. The range of soil cation exchange capacity was 22-30 cmol(+) kg-1 and classified as high soil cation exchange capacity. Rice productivity in the salt-affected soil was around 4 t ha-1. Strategies for soil and controlling plants, such as soil amelioration and salt-tolerant rice cultivars, should be pursued to support plant growth and enhance rice productivity in the salt-affected soil, particularly in the coastal area.